STRATEGI KOMUNIKASI PEMASARAN PERUMAHAN BUMI AS SYIFA DAYA KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This thesis discusses the Marketing Communication Strategy for Bumi As Syifa Daya Housing in Makassar City. The main topic of discussion is how the marketing communication strategy is carried out by Bumi As Syifa Daya Housing in Makassar City and what are the supporting and inhibiting factors in marketing their housing products. The purpose of this study is to explain the marketing communication strategy used by Bumi As Syifa Daya Housing in Makassar City and to find out what factors support and hinder the marketing of Bumi As Syifa Daya Housing in Makassar City. This type of research is included in qualitative descriptive research using a research approach, namely the marketing communication approach. The results of this study indicate that: the marketing communication strategy used by Bumi As Syifa Daya housing includes 1) marketing communication mix, namely: a) sales promotion, b) advertising, c) publicity and d) direct marketing. 2) the supporting factors are: a) cooperating with property agents, b) having different characteristics and complete facilities, c) 100% sharia housing that does not apply confiscation, fines, or interest. 3) The inhibiting factors are a) the lack of public education about sharia property, b) the road conditions are not good enough to pass, c) and the DP is too high.